2018
DOI: 10.1016/j.ejvssr.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Gastric Artery Aneurysm

Abstract: IntroductionAneurysms of small abdominal vessels are extremely rare; however, even minor aneurysmal accessory arteries can rupture, leading to potentially fatal consequences. The purpose of this paper is to report a case of coil embolisation of an aneurysmal posterior gastric artery.Case presentationThe authors describe the case of a 66 year old female patient with an aneurysm of the posterior gastric artery. Coil embolisation was performed. The six month follow up computed tomography angiogram revealed exclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…An aneurysm of the PGA has been reported in the literature. Gomes et al reported an incidental finding of a PGA that was treated by coil embolisation (Gomes et al, 2018). It is recommended to treat all gastric artery aneurysms as they present a high risk of bleeding (Chaer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…An aneurysm of the PGA has been reported in the literature. Gomes et al reported an incidental finding of a PGA that was treated by coil embolisation (Gomes et al, 2018). It is recommended to treat all gastric artery aneurysms as they present a high risk of bleeding (Chaer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%